Skin Hyperpigmentation as the Presenting Symptom of Subacute Combined Degeneration of the Spinal Cord - Abdulhameed Alhazmi; Abdulrahman Almalki; Safieeldin Ghazala (Case Reports in Neurological Medicine)
Vitamin B12 deficiency results in hematological, neurological, and rarely dermatological complications. Subacute combined degeneration of the cord is one of the neurological complications, and usually the presenting symptom is paresthesia. Herein, we report a case of a 46-year-old man with subacute combined degeneration presenting with knuckle hyperpigmentation.